Experimental investigation on the performance of a novel thermo-mechanical refrigeration system driven by an expander-compressor unit - Ahmad K. Sleiti (14778229) (2022)
Operating thermos-mechanical refrigeration (TMR) ejector-based and organic Rankine cycle-based refrigeration systems at ultra-low temperature heat source (60 °C to 100 °C) is challenging and limited by their low coefficient of performance (COP), instability, and high cost. To overcome these limitations, an innovative TMR system consists of a power loop coupled with a cooling loop through an expander-compressor unit (ECU) was introduced. To ensure the efficient operation, reliability, and flexibility, of the ECU-based TMR system, a thorough experimental investigation is presented in this study. In the present setup, an air compressor is used to provide pressurized air to drive the ECU at a desired pressure of 620 kPa. Using R134a as a refrigerant, the performance of the ECU-based refrigeration system is systematically tested for various operating conditions including refrigerant mass, evaporator pressure, temperature and flow rate of the water used for evaporation and condensation loads. All tests are performed at two operating frequencies of the ECU (0.50 Hz and 0.33 Hz). Over a wide range of testing conditions, the results show that the average COP Hz varies from 1.57 to 2.73 at 0.50 Hz and from 1.56 to 2.39 at 0.33 Hz. Moreover, the evaporator temperature reaches less than −10 °C at 0.50 Hz and −9.60 °C at 0.33 Hz. These experimental results prove that the COP of the ECU-based refrigeration system is three times higher than the ejector-based systems and 2.70 times higher than the organic Rankine cycle-based systems. Other Information Published in: Applied Thermal Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.applthermaleng.2022.118635